Learning Module Development using Android Technology Application based on Interactive White Board on Preschool Reading Proficiency: Theoretical framework review: Pembangunan Modul Pembelajaran menggunakan Aplikasi Teknologi Android berasaskan Papan Putih Interaktif terhadap Kemahiran Membaca Kanak-kanak Prasekolah: Ulasan kerangka teori - Baharudin, Haiza Hayati; Masnan, Abdul Halim; Zain, Azizah (Jurnal Pendidikan Bitara UPSI, 2021)
This study aims to provide a review related to the theoretical framework used to develop learning modules using technology of android appplication and interactive whiteboard (IWB) on reading skills of preschool children. Data were obtained through a literature review related to Robert’s Gagne’s Teaching Theory (1985), IEPC Learning Strategies (Wood, 2002), Dual-Coding Theory (Paivio, 1971) and The National Preschool Standard Curriculum (KSPK) used as a guide to the development of this module. The results of the study show that the combination of these three theories and KSPK in the development of modules using IWB technology and android application ( learning to read) will form a comprehensive reading skills learning module in improving reading skills of preschool children as well as the quality of teaching. This review paper suggests that learning developmet modules need to make theories related to teaching strategies balanced from the aspect of caring for the quality of teaching teachers and also the quality of student learning.